(untitled) (Research, Society and Development, 2020)
The objective of this work is to analyze the struggle of the workers movement in Japan after the Second World War and how, from its defeat, it was possible for Toyotism and the labor union by company to emerge, in opposition to an “consensus” ideology, of “Japanese culture”, of “authority”, brought by several authors and that would be at the base of the harmony of the current labor relations in Japan. This research is strictly bibliographic and revision of the historical and sociological literature about the workers movement and toyotist labor relations. As a result of our research, we saw that, unlike the “consensus” and “Japanese culture” theorists, the implantation of Toyotism as a new capitalist work process was only possible with the defeat of one of the most combative workers movements in the world, the Japanese, with a long tradition of struggle since the end of the 19th century. “Just in time”, “kanban”, “labor union - company”, are categories that end years of class struggle in post-war Japan, and not just “dead” categories.